On the relationship between collagen- and carbonate-derived carbon isotopes with implications for the inference of carnivore dietary behavior - DeSantis, Larisa R. G.; Feranec, Robert S.; Southon, John; Cerling, Thure E.; Harris, John; Binder, Wendy J.; Cohen, Joshua E.; Farrell, Aisling B.; Lindsey, Emily L.; Meachen, Julie; Robin O'Keefe, Frank; Takeuchi, Gary T. (Frontiers in Ecology and Evolution, 2022)
Studies of Rancho La Brea predators have yielded disparate dietary interpretations when analyzing bone collagen vs. enamel carbonate—requiring a better understanding of the relationship between stable carbon isotopes in these tissues. Stable carbon isotope spacing between collagen and carbonate (Δca-co) has also been used as a proxy for inferring the trophic level of mammals, with higher Δca-co values indicative of high carbohydrate consumption. To clarify the stable isotope ecology of carnivorans, past and present, we analyzed bone collagen (carbon and nitrogen) and enamel carbonate (carbon) of extinct and extant North American felids and canids, including dire wolves, sabertooth cats, coyotes, and pumas, supplementing these with data from African wild dogs and African lions. Our results reveal that Δca-co values are positively related to enamel carbonate values in secondary consumers and are less predictive of trophic level. Results indicate that the foraging habitat and diet of prey affects Δca-co in carnivores, like herbivores. Average Δca-co values in Pleistocene canids (8.7+/-1‰) and felids (7.0+/-0.7‰) overlap with previously documented extant herbivore Δca-co values suggesting that trophic level estimates may be relative to herbivore Δca-co values in each ecosystem and not directly comparable between disparate ecosystems. Physiological differences between felids and canids, ontogenetic dietary differences, and diagenesis at Rancho La Brea do not appear to be primary drivers of Δca-co offsets. Environmental influences affecting protein and fat consumption in prey and subsequently by predators, and nutrient routing to tissues may instead be driving Δca-co offsets in extant and extinct mammals.